Political risks and foreign direct investments by multinational corporations: A reference point approach. (9th June 2020) - Yasuda, Naoki; Kotabe, Masaaki
Abstract: Research Summary: The purpose of this study is to develop a behavioral framework for management decision‐making under bounded rationality to analyze foreign direct investments and political risks in host countries. This study shows that managers construct reference points on political risks and assess actual political risks in host countries relative to these reference points. This study considers that the political risk reference point is a mental map made up of (a) perceived political risks in host countries where multinational corporations (MNCs) operate and (b) home country political risks. We find that MNCs interpret political risks in host countries as opportunities (threats) if the political risks are below (above) their reference points. Our study provides a significant contribution to the literature on microfoundations of location strategy. Managerial Summary: Prior empirical studies have found both positive and negative effects of political risks on MNCs' investments. This study develops a behavioral framework for MNCs' boundedly rational decision‐making in political risk assessment. Characterizing political risks in host countries by the concept of a political risk reference point resolves the contradictory findings in the literature. Using data from the global mining industry, we find that MNCs interpret political risks in host countries as opportunities (threats) if the political risks are below (above) their PRRPs. We also show that the other competing companies' reference points do not have significant effects on MNCs' investment decisions. These findings offer managerial implications because they help managers predict competitors' actions.